Seasonal Variation of Benthic Diatom Diversity in 2011-2012 and Establishment of Water Quality Index of Yom River - Ekkachai Yana (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Seasonal variations in terms of benthic diatom diversity and establishment of water quality index of Yom River in 2011-2012 were investigated and the water quality assessment for the Yom River was done monthly, from June 2011-May 2012. In this study, 164 species of benthic diatoms were found belonging to 31 genera. The dominant genus of all species were Achnanthidium, Cocconeis, Cymbella, Gomphonema, Gyrosigma, Navicula, Nitzschia, Planothidium, Seminavis and Ulnaria. Thirteen species were considered new records for Thailand, i.e. Achnanthidium caravalense Novais et Ector, Achnanthidium latecephalum Kobayasi, Achnanthidium straubianum Lange-Bertalot, Cymbella parva (Smith) Wolle, Navicula tenera Hustedt, Encyonema hustedtii Krammer, Mayamaea agrestis Hustedt, Navicula acephala Schoeman, Navicula amphiceropsis Lange-Bertalot & Rumrich, Navicula jacobii Manguin, Navicula perventralis Hustedt, Navicula suprinii Moser and Navicula teneloides Hustedt. Moreover, 104 taxa of benthic diatoms were used for the establishment of the Yom River Index based on the main parameters, i.e. BOD5 and nutrients using the indicator value method (IVM) and the weight averaged method (WAs). As a result, the trophic status of the Yom River using the Yom River Index was classified as being in the range of oligo-mesotrophic and mesotrophic status (clean-moderate to moderate water quality).